(Re)Production of Knowledge for Human Resource Building: The Multicultural Dynamics of the Indonesian-language Wikipedia - Christopher Allen Woodrich (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Access to information is a fundamental requirement for developing quality humanresources. One prominent source of such information is Wikipedia, a website whichadvertises itself as